Reducing the Delay Time and Tracking Trajectory of the Robot SCARA Using the Fractional PID Controller - Yassine Bensafia; Abdelhakim Idir; Khatir Khettab (Science, Engineering and Technology)
In recent years, there has been a significant increase in the study of fractional systems and fractional-order control (FOC), which has proven effective in enhancing plant dynamics, particularly in terms of disturbance rejection and response time improvement. Traditionally, the Proportional-Integral-Derivative (PID) controller has been valued for its simplicity and ease of parameter adjustment. However, as the complexity of control systems escalates, several specialised PID controllers have been designed to address specific challenges. Despite its effectiveness, the conventional PID controller often faces limitations in complex systems requiring high precision and adaptive dynamics. Researchers have increasingly focused on the Fractional Proportional-Integral-Derivative (FPID) controller to address these deficiencies. The FPID controller incorporates fractional integrators and derivatives, facilitating improved tuning of system dynamics and offering increased control over response characteristics. This study introduces a fractional integrator in PID control to improve trajectory tracking and reduce delay time in Selective Compliance Articulated Robot Arm (SCARA) systems. Unlike traditional PID controllers, which may struggle with high-frequency noise and parameter variations, the fractional integrator offers enhanced noise suppression and adaptability. The fractional PID approach is relevant beyond robotics, including many systems like temperature control, electrical motor regulation, power electronics, and biomedical control systems, where accuracy and resilience to disturbances are essential. Unlike traditional PID, the proposed technique offers more adaptability in handling transient responses and greater disturbance suppression, making it a viable solution for modern, complex control environments.